Pointwise Hölder exponents of a model for skin laser Doppler flowmetry signals based on six nonlinear coupled oscillators with linear and parametric couplings: Comparison with experimental data from young healthy subjects - Buard, B.; Humeau, A.; Rousseau, D.; Chapeau-Blondeau, F.; Abraham, P. (Ingénierie et recherche biomédicale, 2010)
We study pointwise Hölder exponents of experimental and numerically simulated skin laser Doppler flowmetry (LDF) data that give a peripheral view of the cardiovascular system. The experimental signals are recorded in the forearm of young healthy subjects. The numerically simulated LDF data are computed from a model containing six nonlinear coupled oscillators reflecting six almost periodic rhythmic activities present in experimental LDF signals. Simulated LDF signals are for the first time generated with both linear and parametric couplings in order to represent cardiovascular system behaviors. Moreover, we propose the use of a parametric generalised quadratic variation (GQV) based estimation method for the estimation of the pointwise Hölder exponents. The latter identify possible multifractal characteristics of data. The GQV method is first tested on a white noise measure and then applied on the LDF data. The results of our signal processing analysis show that experimental LDF signals recorded in the forearm are weakly multifractal for young healthy subjects at rest. Furthermore, our findings show that the simulated data have a complexity similar to the one of signal recorded in young healthy subjects. However, their pointwise Hölder exponents have differences that we explain. This paper provides useful information to go deeper into the modeling of LDF data, which could bring enlightenment for a better understanding of the peripheral cardiovascular system. Nous analysons dans cet article la complexité des signaux laser Doppler qui donnent une vue périphérique du système cardiovasculaire. Pour cela, des signaux laser Doppler expérimentaux et simulés numériquement sont étudiés. Les signaux expérimentaux sont enregistrés sur l’avant-bras de sujets sains jeunes. Les données simulées sont générées à partir d’un modèle contenant six oscillateurs non linéaires couplés reflétant six activités quasi périodiques présentes dans les signaux expérimentaux. Dans le modèle, les oscillateurs sont couplés avec deux types de couplages, linéaires et paramétriques, afin de représenter au mieux le comportement du système cardiovasculaire. À notre connaissance, de tels signaux n’ont encore jamais été présentés. La complexité de tous les signaux (expérimentaux et simulés) est étudiée par l’estimation des exposants ponctuels de Hölder. Ces derniers identifient des caractéristiques multifractales des données. Les exposants ponctuels de Hölder sont estimés à l’aide d’une méthode basée sur une variation quadratique généralisée paramétrée, préalablement testée sur une mesure de bruit blanc. Les résultats de notre analyse montrent que les signaux laser Doppler expérimentaux enregistrés sur l’avant-bras sont faiblement multifractals pour des sujets sains jeunes au repos. En outre, nos constatations montrent que les données simulées reflètent une complexité similaire à celle des signaux obtenus sur des sujets sains jeunes. Leurs exposants ponctuels de Hölder ont, cependant, des différences que nous explicitons. Cet article fournit des informations utiles pour aller plus loin dans la modélisation des données laser Doppler, ce qui pourrait apporter des éclaircissements pour une meilleure compréhension du système cardiovasculaire périphérique.